2021
DOI: 10.1038/s41598-021-99276-y
|View full text |Cite
|
Sign up to set email alerts
|

Utility of neutrophil CD64 in distinguishing bacterial infection from inflammation in severe alcoholic hepatitis fulfilling SIRS criteria

Abstract: To assess utility of neutrophilCD64 (nCD64) expression in differentiating bacterial infection from inflammation in patients with severe alcoholic hepatitis (SAH) fulfilling systemic inflammatory response syndrome criteria. Patients with SAH and infection (n = 58), SAH without infection (n = 70), and healthy controls (n = 20) were included. Neutrophil CD64 expression by flowcytometry, serum Procalcitonin (ELISA) and C-reactive protein (Nephelometry) and neutrophil–lymphocyte ratio (NLR) were studied. Percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Normally, CD64 expression is very low in neutrophils, but the expression is significantly induced in peripheral blood neutrophils during bacterial infection and helps in neutrophil phagocytosis and sterilization [ 19 , 20 ]. Many studies show that CD64 has high specificity in bacterial infection, which is helpful in early diagnosis of bacterial infection and the degree of infection [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, CD64 expression is very low in neutrophils, but the expression is significantly induced in peripheral blood neutrophils during bacterial infection and helps in neutrophil phagocytosis and sterilization [ 19 , 20 ]. Many studies show that CD64 has high specificity in bacterial infection, which is helpful in early diagnosis of bacterial infection and the degree of infection [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pander G et al. indicated that quantitative detection of nCD64 in patients with severe alcoholic hepatitis could more accurately identify systemic bacterial infections and inflammation compared to other inflammatory markers ( 22 ). Consistently, our study also showed that KTRs with bacterial infections had significantly higher nCD64 and CD64 index than those with viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some researches showed that nCD64 expression performed good diagnostic efficacy in bacterial infections and sepsis ( 22 ). In a prospective observational study, it concluded that serial measurement of nCD64 expression could facilitate sepsis diagnosis and monitor the clinical course in critically ill patients ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“… 65 Numerous studies have shown an increase in neutrophils in the circulation and in the liver of ALD patients, and neutrophil levels correlate with disease severity and poor clinical outcomes in ALD patients. 66 , 67 Chronic ethanol feeding in mice induces peripheral blood and liver neutrophil infiltration, which is associated with liver injury. 68 Neutrophil aggregation is thought to cause severe hepatocyte damage by promoting macrophage recruitment and interaction with antigen-presenting cells.…”
Section: Neutrophil Recruitment In Aldmentioning
confidence: 99%